Digital Pakistan: opportunities & challenges (Journal of Information Systems and Technology Management, 2008)
IT has revolutionized the social and organizational life around the globe. Given the newness of IT as a technology, there is a lot of potential that needs to be explored. It is however, argued that as IT can revolutionize the economic development, by the same coin, although its mismanagement in adoption process can end up in problems or even straight failure of the technology at the business-end. This study was conducted with reference to opportunities and challenges in the IT adoption process in Pakistan. The aim of the study was to point out the barriers that are impeding the country's computerization process in order to provide facts to the policy makers for smooth computerization. The primary data collected through structured questionnaires was analyzed and tested through correlation, regressions analysis and t-test. Out of 10 hypotheses, 3 were accepted while in the rest null hypotheses were not substantiated. Based on primary and secondary data analysis this study has found that all independent bureaucratic, political, education and social and cultural variables are mutually correlated and have significant impact on shaping and reshaping of IT in Pakistan, while the Pakistan IT policy is inconsistent, administrative machinery attitude is negative and non cooperative, procedures are cumbersome and implementation is weak and ineffective, not to mention the lack of IT knowledge on the bureaucratic side. The political environment is instable and law and order is worse which is discouraging the investment. Moreover, physical and legal infrastructure is insufficient and the country is lacking good quality IT professionals. IT organization alignment is another serious issue in Pakistan. However, government incentives and growing interest from the private sector indicate positive attitude towards computerization of the country.